Crack repair method for building finished with a carbonation-resistant coating

KR103030367B1Active Publication Date: 2026-10-13SEOHAN ENTERPRISE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020260046816
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-03-16
Publication Date
2026-10-13
Estimated Expiration
2046-03-16

Smart Images

  • Figure 112026031619361-PAT00001_ABST
    Figure 112026031619361-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a novel method for repairing cracks in a building that effectively repairs cracks in a building to prevent further cracking or lifting, and also prevents carbonation of the concrete building, thereby extending the service life of the building. The method comprises: a pretreatment process for removing a lifted coating film from a cracked area of ​​the building's exterior wall; a primer application process for applying a water-soluble primer to the cracked area; a first thermal elastic putty application process for applying thermal elastic putty over the primer applied in the first process; a crack repair tape attachment process for attaching a crack repair tape by pressing it onto the thermal elastic putty layer before the thermal elastic putty layer applied in the first process hardens; a second thermal elastic putty application process for additionally applying thermal elastic putty over the first-applied thermal elastic putty layer to embed the crack repair tape inside the thermal elastic putty; and a process of painting the entire exterior wall of the building with a water-soluble primer. and a neutralization prevention paint application process of applying the neutralization prevention paint over the above-mentioned water-soluble primer;
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for repairing cracks in a building by finishing with a neutralization-preventing paint. It is a new method for repairing cracks in a building that effectively repairs existing cracks to prevent further cracking or lifting, as well as preventing neutralization of concrete buildings. Background Technology

[0002] Generally, cracks occur in concrete buildings due to aging and deterioration; if left untreated, water seeps into the cracks, causing structural problems such as corrosion of rebar and shortening the building's lifespan.

[0003] Therefore, if cracks occur in a building, the affected area must be repaired. Typically, when repairing cracks, a waterproofing material is applied to the cracked area, and waterproof tape is attached along the crack to repair it.

[0004] However, conventional waterproofing tapes have the disadvantage of poor durability, causing them to tear and become damaged within a relatively short time after installation, detach from the surface, and re-damage the repaired area, leading to further crack progression.

[0005] Meanwhile, the deterioration of concrete structures is caused by external factors; specifically, environmental factors such as temperature changes, freeze-thaw cycles due to seasonal changes, rainfall, humidity, and changes in atmospheric conditions are the primary causes, while factors such as carbonation, chloride intrusion, rebar corrosion, freeze-thaw cycles, sulfuric acid intrusion, and alkali-aggregate reaction also contribute to the deterioration.

[0006] The concrete deterioration factors described above act individually or in combination, allowing moisture or other harmful external substances to penetrate into the concrete. This leads to the deterioration of the concrete itself or causes corrosion of reinforcing steel, resulting in a decline in the performance of the concrete structure. Furthermore, if the deterioration and cracking of the concrete structure become severe, it poses a risk of ultimately causing the structure to collapse.

[0007] Carbonation, which can be considered a major cause of concrete deterioration, occurs when water or carbon dioxide from the air penetrates into the concrete, gradually releasing calcium hydroxide from within the concrete. This weakens the CSH (calcium silicate hydrate) crystals, leading to a loss of alkalinity and the progression of carbonation. As carbonation progresses, cracks are damaged and the gaps widen. Subsequently, the rebar becomes exposed through these gaps and proceeds to corrosion. Once the rebar begins to corrode, volume expansion due to rust occurs, and the resulting expansion pressure exceeds the stress of the concrete, causing new cracks. These new cracks further accelerate carbonation, rapidly weakening the durability of the concrete structure. Prior art literature

[0008] Republic of Korea Registered Patent No. 10-1974081 (April 24, 2019) Republic of Korea Registered Patent No. 10-2562993 (July 31, 2023) Republic of Korea Registered Patent No. 10-2914079 (January 13, 2026) The problem to be solved

[0009] The present invention is proposed in response to the aforementioned problems, and more specifically, provides a new method for repairing cracks in buildings that not only effectively repairs existing cracks to prevent further cracking or lifting, but also prevents the neutralization of concrete buildings, thereby extending the service life of the buildings. means of solving the problem

[0010] According to the features of the present invention, a method for repairing cracks in a building finished with a neutralization-preventing paint is provided, comprising: a pretreatment process for removing a lifted coating film from a cracked area of ​​the building's exterior wall; a primer application process for applying a water-soluble primer to the cracked area; a first thermal insulation elastic putty application process for applying a thermal insulation elastic putty over the primer applied in the first process; a crack repair tape attachment process for attaching a crack repair tape by pressing it onto the thermal insulation elastic putty layer before the thermal insulation elastic putty layer applied in the first process hardens; a second thermal insulation elastic putty application process for additionally applying a thermal insulation elastic putty over the first applied thermal insulation elastic putty layer to embed the crack repair tape inside the thermal insulation elastic putty; a process of painting the entire exterior wall of the building with a water-soluble primer; and a neutralization-preventing paint application process for applying a neutralization-preventing paint over the water-soluble primer.

[0011] According to another feature of the present invention, the crack repair tape comprises an elastic mesh layer (12) and a non-elastic reinforcing mesh layer (16) attached on the elastic mesh layer (12), the non-elastic material having a relatively higher rigidity than the elastic mesh layer (12).

[0012] According to another feature of the present invention, the non-stretchable reinforcing mesh layer (16) is formed with a narrower width than the stretchable mesh layer (12), and protrusions (13) are formed at both ends of the stretchable mesh layer (12) in the width direction that protrude more than the non-stretchable reinforcing mesh layer (14).

[0013] According to another feature of the present invention, the elastic mesh layer (12) is made of a mesh sheet of an elastic material, and the non-elastic reinforcing mesh layer (16) is made of a glass fiber mesh sheet.

[0014] According to another feature of the present invention, the thermal insulation elastic putty comprises 35 to 60 parts by weight of a water-based binder mixed in a weight ratio of 1:1:1 of an acrylic emulsion, an acrylic-silicone emulsion, and a polyurethane emulsion; 20 to 25 parts by weight of a modified latex-based adhesion enhancer; 5 to 20 parts by weight of an inorganic thermal insulation agent selected from one or more of aluminum oxide, titanium dioxide, calcium carbonate, diatomaceous earth, perlite, expanded vermiculite, and volcanic ash; and 3 to 15 parts by weight of a hollow ceramic biscuits.

[0015] The above anti-neutralization paint comprises, for every 100 parts by weight of acrylic emulsion resin, 20 to 50 parts by weight of water-soluble polyurethane resin, 0.1 to 1 part by weight of silane-based binder, 10 to 20 parts by weight of isododecane, 10 to 20 parts by weight of magnesium silicate, 10 to 20 parts by weight of tungsten oxide, 1 to 10 parts by weight of nano silica, 0.5 to 5 parts by weight of titanium-zirconium nano composite metal oxide, and 1 to 10 parts by weight of scoria. Effects of the invention

[0016] The present invention, having the above-described composition, can effectively repair cracked areas using thermal insulation elastic putty and crack repair tape, and achieve the following effects by finishing with a neutralization-preventing paint.

[0017] First, since the thermal insulation elastic putty possesses excellent adhesion, waterproofing, thermal insulation, and elasticity, it offers superior repair performance for cracks; in particular, due to its thermal insulation properties, the shrinkage and expansion of concrete caused by temperature changes are reduced, thereby preventing the recurrence of cracks.

[0018] Second, by using a crack repair tape composed of an elastic mesh layer and a non-elastic reinforcing mesh layer, the elastic mesh layer flexibly follows the micro-deformation of the concrete, while the non-elastic reinforcing mesh layer provides structural rigidity, thereby exerting a tensile reinforcement effect on the cracked area, and thus effectively preventing the occurrence of secondary cracks.

[0019] Third, the crack repair tape is embedded between the thermal insulation elastic putty layers, and in particular, the thermal insulation elastic putty flows through the mesh of the crack repair tape to form an integrated structure between the thermal insulation elastic putty layers and the crack repair tape; therefore, lifting or peeling of the crack repair tape does not occur, and the cracked area is effectively repaired.

[0020] Fourth, by applying a neutralization prevention paint to the entire exterior wall of the building, carbon dioxide and chlorides in the air are prevented from penetrating into the concrete, thereby preventing the neutralization of the concrete and delaying the corrosion of the reinforcing steel, which improves the structural safety and durability of the building and extends its service life. Brief explanation of the drawing

[0021] FIG. 1 is a photograph of a crack repair tape used in a preferred embodiment of the present invention. Figure 2 is a disassembled photograph of the crack repair tape above. Specific details for implementing the invention

[0022] The present invention will be described in more detail below.

[0023] The process according to a preferred embodiment of the present invention is carried out as follows.

[0024] (1) Preprocessing

[0025] Remove the peeling coating from the cracked areas of the building's exterior wall. Preferably, the contaminants on the building's exterior wall are completely removed using a high-pressure washer or similar equipment, and then the peeling coating from the cracked areas is peeled off or ground down with a grinder to remove it.

[0027] (2) Application process of water-soluble primer

[0028] A water-soluble primer is applied to cracks in the exterior walls of a building to improve the adhesion of the thermal insulation elastic putty applied thereon. Since water is used as a diluent and dispersant, the water-soluble primer has low odor, good workability, and environmentally friendly advantages, making its use in this invention preferable. In this process, the type of water-soluble primer that can be used is not particularly limited, and a suitable one is selected from known water-soluble primers.

[0029] (3) First application process of thermal insulation elastic putty

[0030] Insulating elastic putty is applied to the cracked area to form an insulating elastic putty layer, and the crack is filled with insulating elastic putty. In this process, insulating elastic putty is used that comprises 35 to 60 parts by weight of a water-based binder, 20 to 25 parts by weight of a modified latex-based adhesion enhancer, 5 to 20 parts by weight of an inorganic insulating agent, and 3 to 15 parts by weight of hollow ceramic beads.

[0031] In this thermal insulation elastic putty, the water-based binder is a mixture of an acrylic emulsion, an acrylic-silicone emulsion, and a polyurethane emulsion in a weight ratio of 1:1:1, which imparts adhesion, water resistance, and elasticity to the thermal insulation elastic putty. Furthermore, the modified latex-based adhesion enhancer is intended to improve the elasticity of the thermal insulation elastic putty along with the adhesion, and the modified latex-based adhesion enhancer consists of styrene-acrylic latex, SBR-modified acrylic latex, urethane-modified acrylic latex, etc.

[0032] In addition, at least one of aluminum oxide, titanium dioxide, calcium carbonate, diatomaceous earth, perlite, expanded vermiculite, and volcanic ash is used as the inorganic insulating material. Furthermore, at least one of the hollow ceramic beads selected from the group consisting of borosilicate glass, aluminosilicate, and silicate is used. Due to these inorganic insulating materials and hollow ceramic beads, the thermal insulation elastic putty has excellent thermal insulation properties.

[0033] Thermal elastic putty having this composition possesses not only adhesion but also excellent waterproofing and thermal insulation properties, as well as elasticity. In particular, since the thermal elastic putty has thermal insulation properties, shrinkage and expansion due to external temperatures are reduced, preventing cracks from recurring in cracked areas.

[0034] (4) Crack repair tape application process

[0035] In the above process, crack repair tape is attached to the thermal insulation elastic putty layer applied.

[0036] Preferably, in this process, a crack repair tape (10) is used, consisting of an elastic mesh layer (12) as disclosed in FIGS. 1 and 2, and a non-elastic reinforcing mesh layer (16) attached to the elastic mesh layer (12) with an adhesive layer formed on the bottom surface. The elastic mesh layer (12) is made of a mesh sheet made of an elastic material such as spandex or a polyester and spandex blend. Since the elastic mesh layer (12) has elasticity, it stretches in accordance with the behavior of the concrete due to shrinkage and expansion. It is preferable to use a mesh sheet made of a polyester and spandex blend as the elastic mesh layer (12) so that the elastic mesh layer (12) has durability in addition to elasticity.

[0037] The above-mentioned non-stretchable reinforcing mesh layer (16) is a layer that provides structural strength to the crack repair tape and is made of a non-stretchable mesh sheet having higher rigidity than the stretchable mesh layer (12). Preferably, the non-stretchable reinforcing mesh layer (16) is made of a glass fiber mesh sheet, and particularly preferably, it is made of a glass fiber mesh sheet with a smaller mesh and larger pores compared to the stretchable mesh layer (12). Also, as illustrated, the non-stretchable reinforcing mesh layer (16) is formed with a narrower width than the stretchable mesh layer (12), so that protrusions (13) protruding more than the non-stretchable reinforcing mesh layer (16) are formed on both sides of the stretchable mesh (12). In some cases, the length of the stretchable mesh layer (12) is formed shorter than the length of the non-stretchable mesh layer (12), so that protrusions protruding more than the non-stretchable reinforcing mesh layer (16) may also be formed at both ends in the longitudinal direction of the stretchable mesh window (12).

[0038] Since these protrusions (13) are made only of the elastic mesh layer (12), the protrusions (13) have higher flexibility and elasticity compared to the part laminated with the non-elastic reinforcing mesh layer (16) of the elastic mesh layer (12), so they have excellent conformability to the minute movements of the concrete due to temperature changes. Therefore, when protrusions (13) made only of the elastic mesh layer (12) are formed on both ends of the crack repair tape in this way, the ends of the crack repair tape follow the movements of the concrete more effectively, so the occurrence of secondary cracks is effectively prevented, and the protrusions (13) are embedded into the thermal elastic putty layer, providing an anchor effect, and since stress concentration at the boundary of the crack repair tape is prevented, the edges of the crack repair tape are prevented from lifting or peeling, and thus the structural stability and adhesion of the entire crack repair tape (10) are improved.

[0039] This non-stretchable reinforcing mesh layer (16) is attached to the elastic mesh layer (12) on the adhesive layer formed on the bottom surface, so that the elastic mesh layer (12) and the non-stretchable reinforcing mesh layer (16) are stacked vertically.

[0040] The crack repair tape (10) of this configuration can simultaneously secure flexibility and strength because the elastic mesh layer (12) flexibly follows the micro-deformation of the concrete and the thermal elastic putty layer, while the non-elastic reinforcing mesh layer (16) provides rigidity. That is, it can flexibly follow the deformation caused by shrinkage and expansion of the concrete due to temperature changes, while simultaneously providing tensile reinforcement effects for the crack. Therefore, the occurrence of secondary cracks around the crack is prevented.

[0041] In this process, a crack repair tape is attached to the thermal insulation elastic putty layer before the first applied thermal insulation elastic putty layer hardens. The crack repair tape is placed along the crack, and then the crack repair tape is pressed.

[0043] (5) Second application process of thermal insulation elastic putty

[0044] A second layer of thermal elastic putty is applied over the crack repair tape to embed the crack repair tape into the thermal elastic putty. In this way, the crack repair tape (10) is embedded between the first layer of thermal elastic putty and the second layer of thermal elastic putty, and the thermal elastic putty flows into the mesh of the elastic mesh layer (12) and the non-elastic reinforcing mesh layer (14) of the crack repair tape (10), thereby obtaining an anchor effect. Thus, the crack repair tape and the thermal elastic putty form an integrated structure, and the attachment state of the crack repair tape is firmly maintained.

[0045] The repair of the crack itself is completed through this second application process of thermal insulation elastic putty.

[0046] (6) Application of water-soluble primer to the entire exterior wall

[0047] In this process, a water-soluble primer is applied to the entire exterior wall of the building to enhance the adhesion of the anti-neutralization paint applied in the subsequent process.

[0048] The type of water-soluble primer used in this process is not specifically limited, and known water-soluble primers are used.

[0049] (7) Application process of anti-neutralizing paint

[0050] By applying an anti-neutralization paint over the above-mentioned water-soluble primer, the penetration of carbon dioxide and chlorides into the exterior walls of the building, i.e., the concrete, is inhibited, and rebar corrosion is delayed.

[0051] As previously announced, concrete carbonation is a phenomenon in which the pH of concrete drops as carbon dioxide in the air penetrates into the concrete and calcium carbonate is formed. During this process, the reinforcing steel inside the concrete corrodes, threatening the structural safety of the building. To prevent this, anti-carbonation paint is used.

[0052] In this process, a known anti-neutralizing paint may be used, but preferably, an anti-neutralizing paint comprising an acrylic emulsion resin, a water-soluble polyurethane resin, a silane-based binder, isododecane, magnesium silicate, tungsten oxide, nano silica, titanium-zirconium nano composite metal oxide, and scoria is used.

[0053] The above acrylic emulsion resin is the main resin of the anti-neutralization paint. As a copolymer of acrylic acid, methacrylic acid, and styrene, it has transparency greater than that of glass and is lightweight and has excellent processability, so it is desirable to use it as the main resin of the anti-neutralization paint. The above water-soluble polyurethane resin improves the adhesion and waterproofing of the anti-neutralization paint.

[0054] And the above silane-based binder is intended to strengthen the initial adhesion between concrete and the paint composition, and some examples of usable binders include octadecyltrichlorosilane, perfluorodecyltrichlorosilane, perfluorodecyltriethoxysilane, and perfluorooctyltriethoxysilane.

[0055] The above-mentioned isododecane acts as a low-viscosity, low-surface-tension hydrophobic solvent, allowing the paint to penetrate uniformly into the micropores and cracks of the concrete surface, thereby improving the continuity of the coating film. By blocking the permeation pathways of carbon dioxide and moisture, it prevents the neutralization of the concrete and increases the bonding strength between the coating film and the concrete.

[0056] In addition, the magnesium silicate is stable against acids and alkalis and is used to provide chemical stability against acids and alkalis. The tungsten oxide provides a shielding effect against ultraviolet and infrared rays, improves the prevention of carbonation and salt resistance of concrete through interaction with isododecane and magnesium silicate, and suppresses the deterioration of the coating film.

[0057] In addition, the nano silica functions as a UV blocker and improves the density, abrasion resistance, water resistance, and gas barrier properties of the coating film. In particular, it combines with the silane-based binder to contribute to improving the alkali resistance and water resistance of the coating film. Preferably, nano silica with a particle size of 10 to 100 nm is used. Furthermore, the scoria stone has numerous pores and possesses antibacterial and deodorizing functions, thereby preventing contamination of the coating film and the occurrence of mold.

[0058] Furthermore, the above titanium-zirconium nano-mixed metal oxide (TiO2-ZRO2-mixed oxide) is a nanocomposite in which ZRO2 is doped and co-precipitated on TiO2. It possesses excellent corrosion resistance due to its low electrical conductivity and chemical stability. In particular, because it has a much denser amorphous structure compared to cases where titanium oxide and zirconium oxide are used, the long-term neutralization prevention effect of the coating film is enhanced when the titanium-zirconium nano-mixed metal oxide is used.

[0059] When considering physical properties such as adhesion, chemical resistance, weather resistance, and water resistance in addition to the neutralization prevention properties, it is preferable that this anti-neutralization paint comprises 20 to 50 parts by weight of water-soluble polyurethane resin, 0.1 to 1 part by weight of silane-based binder, 10 to 20 parts by weight of isododecane, 10 to 20 parts by weight of magnesium silicate, 10 to 20 parts by weight of tungsten oxide, 1 to 10 parts by weight of nano silica, 0.5 to 5 parts by weight of titanium-zirconium nano composite metal oxide, and 1 to 10 parts by weight of scoria stone, based on 100 parts by weight of acrylic emulsion resin.

[0060] In this way, crack repair is completed by applying anti-neutralization paint to the exterior walls of the building.

[0061] The present invention, having the above-described composition, repairs cracked areas using thermal elastic putty and crack repair tape, thereby reducing the shrinkage and expansion of concrete due to temperature changes. Furthermore, since the crack repair tape flexibly follows the deformation of the concrete while maintaining structural rigidity, the recurrence of cracks is prevented. Additionally, because the surface is finished with a neutralization-preventing paint, the neutralization of the concrete is prevented, improving the structural safety and durability of the structure and extending its service life.

Claims

Claim 1 A pretreatment process for removing lifted coating film from cracked areas of the building's exterior wall; a primer application process for applying a water-soluble primer to the cracked areas; a first thermal elastic putty application process for applying thermal elastic putty over the primer applied in the above process; a crack repair tape attachment process for attaching a crack repair tape to the thermal elastic putty layer by applying pressure before the thermal elastic putty layer applied in the above process hardens; a second thermal elastic putty application process for additionally applying thermal elastic putty over the first-applied thermal elastic putty layer to embed the crack repair tape inside the thermal elastic putty; and a process of painting the entire exterior wall of the building with a water-soluble primer. The method includes a neutralization prevention paint application process in which a neutralization prevention paint is applied over the above-mentioned water-soluble primer; wherein the crack repair tape (10) comprises an elastic mesh layer (12) made of spandex or a blend of polyester and spandex, and a non-elastic reinforcing mesh layer (16) made of a glass fiber mesh sheet attached to the upper surface of the elastic mesh layer (12) and having relatively higher rigidity than the elastic mesh layer (12); wherein the non-elastic reinforcing mesh layer (16) is formed with a narrower width than the elastic mesh layer (12), and protrusions (13) protruding more than the non-elastic reinforcing mesh layer (16) are formed at both ends of the elastic mesh layer (12) in the width direction; and when the thermal insulation elastic putty is applied a second time, the thermal insulation elastic putty flows into the mesh openings of the elastic mesh layer (12) and the non-elastic reinforcing mesh layer (16) and anchors A method for repairing cracks in a building by finishing with a neutralization-preventing paint characterized by exhibiting an anchor effect. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 In claim 1, the thermal insulation elastic putty comprises: 35 to 60 parts by weight of a water-based binder mixed in a weight ratio of 1:1:1 of an acrylic emulsion, an acrylic-silicone emulsion, and a polyurethane emulsion; 20 to 25 parts by weight of a modified latex-based adhesion enhancer; and 5 to 20 parts by weight of an inorganic thermal insulation agent selected from one or more of aluminum oxide, titanium dioxide, calcium carbonate, diatomaceous earth, perlite, expanded vermiculite, and volcanic ash. A method for repairing cracks in a building by finishing with a neutralization-preventing paint, characterized in that the neutralization-preventing paint comprises 3 to 15 parts by weight of hollow ceramic biscuits and, for every 100 parts by weight of acrylic emulsion resin, 20 to 50 parts by weight of water-soluble polyurethane resin, 0.1 to 1 part by weight of silane-based binder, 10 to 20 parts by weight of isododecane, 10 to 20 parts by weight of magnesium silicate, 10 to 20 parts by weight of tungsten oxide, 1 to 10 parts by weight of nano silica, 0.5 to 5 parts by weight of titanium-zirconium nano composite metal oxide, and 1 to 10 parts by weight of pumice stone.

Citation Information

Patent Citations

  • Unidirectional fiber sheet for reinforcing building structure and its manufacture

    JP1999034211A

  • Heat insulating and waterproof construction method of building

    KR1020240069357A

  • Coating composition for Preventing neutralization of concrete structure

    KR102667009B1